Efektivitas Metode Tell Show Do Terhadap Kecemasan Dental Pada Pasien Penambalan Gigi Usia 6-8 Tahun Di RSUD Cibabat Kota Cimahi - Rahmanawati, Teni Gindi; Heriyanto, Yonan; Restuning, Sekar; Fatimah, Siti (Poltekkes Kemenkes Bandung, 2024)
Introduction: Anxiety about dental care begins in children aged 6-8 years (51%) and adolescents (22%). Filling often triggers anxiety in pediatric patients. Using the Tell Show Do method can be an alternative to reduce anxiety in children. This study aimsto determine the effectiveness of the Tell Show Do method on dental anxiety in dental filling patients aged 6-8 years at Cibabat Regional Hospital, Cimahi City. Method: This type of research is pre-experimental with a one group pre and post test design.The research sample of 44 people was taken using accidental sampling technique. Data was collected using the MCDAS questionnaire consisting of 5 questions. Analysis of research data includes bivariate and univariate analysis using the Wilcoxon test. Results: Before being given the Tell Show Do method, 20 child patients (45.5%) had anxiety levels in the moderate anxiety category, whereas after being given the Tell Show Do method intervention, 35 child patients (79.5%) had anxiety levels in the anxious category. light. The results of statistical analysis showed that the p-value was 0.000 < α 0.05, so the Tell Show Do method was effective in reducing dental anxiety.Conclusion: There is an effect of providing the Tell Show Do method intervention on the anxiety level of pediatric tooth filling patients at Cibabat Regional Hospital, Cimahi City.